2022
DOI: 10.1002/cssc.202201553
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Metallic Phosphorus Corrole as Efficient Electrocatalyst in Hydrogen Evolution Reaction

Abstract: The economical consideration of using an electrocatalyst in energy-related field, composed of non-precious/sustainable elements is quite noteworthy. In this work, the phosphorus(V) complex of tris-(pentafluorophenyl)corrole [(TPFC)P V (OH) 2 ] was reported as electrocatalyst for the hydrogen evolution reaction (HER). The electrochemical studies revealed that the HER experienced a ECEC pathway (E: electron transfer step, C: chemical step), and the possible intermediate [P V ]À H species was suggested. (TPFC)P V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…All studied corroles 1P-5P (Synthetic details and characterization see Supporting Information) were well characterized by nuclear magnetic resonance (NMR), high-resolution mass spectroscopy (HRMS) (Figures S1-S13 in the Supporting Information) (4P has been characterized in our previous work). [16] We firstly examined the photophysical properties of 1P-5P via obtaining spectra of ultraviolet-visible spectroscopy (UV/Vis) and fluorescence emission (Figure 1b, c, e). All data are summarized in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studied corroles 1P-5P (Synthetic details and characterization see Supporting Information) were well characterized by nuclear magnetic resonance (NMR), high-resolution mass spectroscopy (HRMS) (Figures S1-S13 in the Supporting Information) (4P has been characterized in our previous work). [16] We firstly examined the photophysical properties of 1P-5P via obtaining spectra of ultraviolet-visible spectroscopy (UV/Vis) and fluorescence emission (Figure 1b, c, e). All data are summarized in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…[15] More recently, our group had probed the HER catalytic efficacy of non-metallic phosphorus corrole and it turned out that phosphorous corrole is a new kind of promising HER molecular catalyst. [16] To explore the effect of peripheral substituents on the electrocatalytic HER activity of phosphorous corrole, we here have prepared a series of phosphorus corroles 1P-5P with different electron structure. The complexes 1P-4P were prepared according to the methods reported previously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorbed on a graphite electrode, this complex catalyzed the HER from aqueous acidic solution at low overpotential (−0.3 V vs NHE), high catalytic turnover numbers (TON ≫ 10 7 ), and a turnover frequency (TOF) of 600 s –1 . Many other transition (such as Mn, Fe, Ni, Cu, Mo, Au) and post-transition (such as P) metallocorroles and even free-base corroles were since examined as HER electrocatalysts under homogeneous and heterogeneous conditions. , In one recent study published by Mizrahi et al, the authors showed that a corrole-fused binuclear iron corrole is a better electrocatalyst than the analogues mononuclear complex . Another development is the 2021 report by Kumar et al, who took advantage of the just disclosed substituent-free corrole (the parent corrole) and its metal complexes .…”
Section: Electrocatalysismentioning
confidence: 99%
“…Previously, we have reported the catalytic activity of pentafluorophenyl and amino, [19] nitro, [15a] cyano, [20] and ethoxycarbonyl [21] substituted cobalt corroles and nonmetallic phosphorus corroles [22] in the electrocatalytic HER. To test whether hydroxyl at meso‐ phenyl substituent can act as a proton relay group in the electrocatalytic HER.…”
Section: Introductionmentioning
confidence: 99%